COSMOS: A web-based repository of Learning Designs for Science Education - Sampson, Demetrios; Zervas, P.; Sotiriou, S. (2011)
Over the past years a large amount of digital science education resources became available worldwide through web-based repositories facilitating their sharing and re-use among science education communities. These resources bare the potential to support technology-enhanced science education by enabling science education teachers to improve their day-to-day science teaching. On the other hand, it has been identified that science education teachers could benefit from their participation in communities of best science teaching practices by sharing, not only digital educational content, but learning designs that reflect their pedagogical practice. This has lead to efforts on moving beyond web-based repositories of digital content towards the development of webbased repositories of learning designs. Nevertheless, sharing learning designs requires tools and strategies, so as to facilitate the representation of these learning designs in a commonly understandable manner between humans and machines. To this end, we present the design and operation of the COSMOS web-based repository of Learning Designs for supporting Science Education Teacher Communities. © 2011 American Scientific Publishers.